2004
DOI: 10.1002/eji.200425092
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of NK cells results in disseminating lethal infection with Bordetella pertussis associated with a reduction of antigen‐specific Th1 and enhancement of Th2, but not Tr1 cells

Abstract: IFN-gamma plays a critical role in protection against Bordetella pertussis, but Th1 cells are only detectable after the infection has started to resolve, suggesting a protective role for innate IFN-gamma early in infection. Here, we demonstrate significant recruitment of NK cells and NKT cells into the lungs following respiratory challenge with B. pertussis. Furthermore, NK cells are the primary source of IFN-gamma in the lungs during the acute stage of infection. Stimulation of IFN-gamma production by NK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 25 publications
8
98
2
1
Order By: Relevance
“…Clearance of B. pertussis from the respiratory tract is mediated by IFN-g secreted by Th1 and NK cells, as well as Ag-specific Ab production (4,8). Furthermore, we demonstrated that adaptive immunity induced by vaccination was dependent on Ag-specific IL-17 production (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearance of B. pertussis from the respiratory tract is mediated by IFN-g secreted by Th1 and NK cells, as well as Ag-specific Ab production (4,8). Furthermore, we demonstrated that adaptive immunity induced by vaccination was dependent on Ag-specific IL-17 production (5).…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive immunity generated by previous infection or immunization with the whole-cell vaccine is effective at preventing severe disease, and studies in a mouse model suggested that a combination of Abs and Th1 and Th17 cells are involved (3)(4)(5)(6)(7). Protection against a primary infection with B. pertussis is mediated by innate and adaptive immune responses, and IFN-g secreted by NK and Th1 cells seems to be critical (4,8,9). However, host immune responses are suppressed, especially early in infection, because of the induction of regulatory T cells (10), as well as by the various immune-subversion strategies evolved by B. pertussis virulence factors to prolong survival in the host (2,11,12).…”
mentioning
confidence: 99%
“…Anti-ASGM1 Ab has been used to deplete NK cells in mice (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). However, it has been known for some time that ASGM1 can be upregulated on leukocytes other than NK cells in the context of viral infection (45).…”
mentioning
confidence: 99%
“…Indeed, the in vivo default mechanism of CD4 ϩ T cells in the absence of NK cells appears to be strongly biased toward the acquisition of a Th2 phenotype. 49,50 In humans, direct evidence for the close contact between NK cells and MDDCs as well as for the ability of NK cells to kill iMDDCs after migration to peripheral tissues has been provided in atopic skin lesions induced by the Malassezia yeast. 51 Finally, it is of note that the encounter between NK cells and different DC subtypes is not limited only to pathogen-invaded peripheral tissues but occurs also in secondary lymphoid compartments.…”
Section: Discussionmentioning
confidence: 99%